Indonesian YouTube Viewers’ Interpretation of the Law of Assumption: A Reception Analysis of Audience Comments - Levina Lailani Suprapto; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study examines how Indonesian YouTube audiences interpret Neville Goddard’s Law of Assumption and explores how creators’ creative domestication strategies shape audience reception. Using a descriptive qualitative approach and content analysis of 250 comments extracted from three YouTube channels, the study applies Venuti’s domestication and foreignization framework. The findings indicate that Republic Creator achieves procedural effectiveness, although this is accompanied by a reduction in meaning. Manifest with Lang demonstrates a balance between conceptual understanding and practical application, while Kunci Hidup reveals conceptual and technical gaps in audience comprehension. Based on the sampled Indonesian YouTube channels analyzed, the results suggest a trade-off between accessibility and depth of understanding when the Law of Assumption is simplified in digital spaces.